CHARACTERISTICS, STABILITY AND ANTIMICROBIAL ACTIVITY OF LACTIC ACID BACTERIA (Leuconostoc sp) ISOLATED FROM BROILER’S CAECUM DURING STORAGE - Sumarsih, S.; Sulistiyanto, B.; Sutrisno, C.I. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
Lactic acid bacteria (LAB) is one of the natural microbe which widely used as fermentation agents.The purpose of this study was to examine the characteristics, stability and antimicrobial properties oflactic acid bacteria (Leuconostoc sp) isolated from broiler’s caecum during storage. This research wasconducted by the Complete Randomized Design with 4 treatments (time of storage: 0, 2, 4 dan 6 weeks)with 12 replications. Parameters observed were total number and stability properties of Leuconostoc spisolate which known as lactic acid bacteria. The results obtained total number of Leuconostoc sp isolatewere significantly (P<0.05) decreased from 8 x 107 to 1 x 103 Colony Forming Unit (CFU)/mL duringstorage. Stability properties of Leuconostoc sp isolate were not affected by the time of storage.Antimicrobial activity of Leuconostoc sp were significantly (P<0.05) decreased from 9.94 to 8.68, 7.23and 6.14 mm during storage at 2, 4 and 6 weeks.